Case report: Unilateral papilledema in a dog with a large suprasellar mass and suspected intracranial hypertension: insights from funduscopy, optical coherence tomography, and magnetic resonance imaging - Cho, Heejong; Choi, Mihyun; Yoo, Sukjong; Jeong, Manbok; Park, Shin Ae (Frontiers in Veterinary Science, 2024)
A spayed, 8-year-old female Poodle, weighing 5.7 kg, was presented with the chief complaint of vision impairment. Vision assessment, including pupillary light reflexes, menace response, dazzle reflex, and maze navigation in photopic and scotopic circumstances, revealed a negative response in both eyes except for positive direct pupillary light reflex in the right eye and positive consensual pupillary light reflex from the right eye to the left eye. Systemic evaluation, including neurologic status, blood profile, and thoracic radiographs, did not reveal any abnormalities. Complete ophthalmic examinations, ocular ultrasonography, and electroretinography did not identify a cause of blindness. Upon funduscopy, the left eye exhibited an increased optic disc diameter, blurred optic disc borders, and loss of the physiologic pit, as well as an increase in vascular tortuosity. In the right eye, there were multifocal depigmented areas in the non-tapetal fundus and several pigmented spots surrounded by a region of dull tapetal reflection in the tapetal fundus. The optical coherence tomography revealed severe anterior deformation of the optic nerve head and Bruch's membrane in the peripapillary region of the left eye. Magnetic resonance imaging revealed an irregular, broad-based suprasellar mass, with features suggestive of intracranial hypertension, including dorsal displacement of third ventricles, a rightward shift of the falx cerebri, transtentorial herniation, perilesional edema, flattening/protrusion of the posterior sclera, and lager optic nerve sheath diameter in left side than right side. This is the first comprehensive report that describes unilateral papilledema in a dog with a brain tumor, using advanced ophthalmic and neuro-imaging modalities.